Travel demand management : a resource book. (AUSTROADS publication, 2002)
Travel demand management has been broadly defined in these guidelines as intervention to modify travel decisions so that more desirable transport, social economic and/or environmental objectives can be achieved and the adverse impacts of travel reduced.